How Sustainable is Environmental Economics? A Review of Research Trends and Implications - Al-Zoubi, Waleed Kalf (International Journal of Energy Economics and Policy, 2024)
Embarking on a comprehensive review of the Environmental Economics literature, we employed a bibliometric approach to gather 6,118 articles published between 1993 and 2023 from Scopus-indexed journals. Leveraging various software tools, including RStudio, VOSviewer, and Excel, we analyzed the data to identify the most active scientific contributors in terms of countries, institutions, sources, documents, and authors. Our examination revealed a notable upward trend in publication starting from 2017, underscoring the increasingly diverse applications of Environmental Economics across domains such as Sustainability, Environmental Footprints, Carbon Emissions, Climate Impact, Navigating Environmental Governance, Policies for Sustainable Futures, Economic Approaches, and Environmental Sustainability. Notably, China, the United States, and the United Kingdom emerged as the top three contributors to the literature. The findings of our study offer valuable insights for market participants, particularly in understanding how Environmental Economics can inform their decision-making processes.